PERLAKUAN TERHADAP ANAK DI DALAM PERUNDANG-UNDANGAN DI INDONESIA (Telaah Kritis Pasal 7 Ayat 1 UU No. 1 Tahun 1974 Tentang Batas Umur Melangsungkan Perkawinan) - Sofia Hardani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
In article 7, paragraph (1) of Law No. 1 of 1974 on marriage mentioned that the maturity of a child is if the man was 21 years old and 18 year old girl. In article 7, paragraph (1) of Law No. 1 of 1974 on marriage states that marriage is only allowed if a man has reached the age of 19 years and women have attained the age of 16 years. That is, the law allows minors to enter into marriage. On the other hand, the law looks acknowledge a violation of the provisions of the age and maturity limits candidates to enter into marriage. It is accommodated in article 7, paragraph (2) of Law No. 1 1974, that court or other officials appointed by the parents of the male and female can give dispensation to the minors to enter into marriage. Inconsistency Law 1 1974 about the age limit can be interpreted as accommodate marriage of underage marriage. Moreover, in Article 7 of the law as well as in his explanation did not mention the reasons that can be used as the basis of given dispensation, so that everyone can easily obtain it. Law's provision is very loose, but when viewed from various aspects, a lot of harm caused by the underage marriage, particularly for women.